Web-augmentation, design thinking, and collaboration engineering to foster innovation in DSS for agriculture: a case study - Urbieta, Matías (2019)
Decision making in agriculture increasingly relies on software, for example to gather important information or to weight alternatives. Information systems innovation in agriculture is a challenging and very active area. Existing software products, frequently implemented as web applications, are found to lack functionality, for example to support collaboration. Augmenting the web is a widely adopted technique for enhancing existing applications with new features which are not available out-of-the-shelf. Design thinking has proven to be an effective tool to support innovation on many domains. Collaboration Engineering is an effective means to reuse design experience of collaboration strategies. This work presents an approach to involve end-users in enhancing exiting web software to produce incremental innovations. The approach relies on Design Thinking, Web Augmentation and Collaboration Engineering. The approach was successfully tried in a case study letting end-users add collaboration support to a system that did not provide it.